HUBUNGAN SOSIAL EKONOMI RUMAH TANGGA TANI DENGAN PENERAPAN AGROFORESTRI DI DESA KAYUUWI KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA - Meldi Djela; Hengki D. Walangitan; Reynold P. Kainde; Wawan Nurmawan (COCOS, 2014)
ABSTRACTRELATIONSHIP BETWEEN SOCIO-ECONOMIC of FARMER’s HOUSEHOLD WITH THE AGROFORESTRY IMPLEMENTATION IN VILALLAGE KAYUUWI SUBDISTRICT KAWANGKOAN WEST MINAHASA DISTRICTThe goal of this research is to describe the level of agroforestry implementation and analyze the relationship between socio-economic of farmer’s households with agroforestry implementation in Village Kayuuwi Subdistrict Kawangkoan West Minahasa District. This study was conducted over two months from May to July 2014.The study was conducted by survey method. Retrieving data using purposive method (deliberately) while agroforestry implementation analyzed descriptively and the chi-square analysis (x2) used for agroforestry associated with socio-economic. The results showed that the rate of adoption of agroforestry are found on farm land unit is passably agroforestry is 43.33% while the less common is a good agroforestry is 16.67%. The level of agroforestry implementation have a relationship with socio-economic factors, which is the non-formal education.Keywords: Agroforestry, Social Economic, Village Kayuuwi.